Al-Qur’an dan Psikologi - Muslim Afandi (Medina-te : Jurnal Studi Islam, 2018)
Viewed from various aspects, al-Qur'an has long talked about psychology before the West exposed this concept. Even when by definition the concept of psychology is still "shifting in search" of the true form of meaning, Al-Qur'an explicitly explains the psychological concepts related to everything that concerns of human both from physical and psychic reviews. Al-Quran reviews about the human physical includes insan, ins, nas or unas, basyar, and bani adam or zurriyat adam. While the review of the soul/psychic is broader that start from an-nafs, ar-ruh and al-jism with all sorts of diversity of meaning and intent. Ditinjau dari berbagai aspek, al-Quran telah lama membicarakan psikologi sebelum dunia Barat memaparkan konsep ini. Bahkan ketika secara definisi konsep psikologi masih “bergeser mencari” bentuk arti yang sesungghuhnya, al-Quran telah secara gamblang menjelaskan konsep-konsep psikologis berkaitan dengan segala sesuatu yang menyangkut manusia baik dari tinjauan fisik maupun psikis. Tinjau al-Quran tentang fisik manusia mencakup insan, ins, nas atau unas, basyar, dan bani adam atau zurriyat adam. Sementara tinjauan tentang jiwa/psikis lebih luas yang dimulai dari an-nafs, ar-ruh dan al-jism dengan segala macam keberagaman arti dan maksudnya.